Penerapan Problem Based Learning untuk Meningkatkan Hasil Belajar Siswa SMKN 1 Sukorejo - Rofiul Arif Widodo; Hasri Hasri; Ruhmah Ruhmah (Celebes Science Education, 2024)
The application of the Problem Based Learning (PBL) learning model to improve the learning outcomes of XII KI 1 class students in the Chemical Industry Process subject. This research is a classroom action research that aims to improve learning outcomes in Chemical Industry Process subjects through the Problem Based Learning Model (PBL). The subjects of this study were XII KI 1 class students of SMK Negeri 1 Sukorejo, totaling 16 students. The method used is discussion with a scientific approach-PBL. Data collection was carried out using observation and evaluation techniques at the end of learning at the end of each cycle. The results of this study indicate that the average value of learning outcomes in the Chemical Industry Process subject of students in class XII KI 1 SMK Negeri 1 Sukorejo at the end of cycle I is an average value of 75.69 with completeness reaching 64.71%, the average value of student learning outcomes in cycle II has increased to 80.56 with completeness reaching 79.41%, and in cycle III the average value reaches the highest value of 84.72 and completeness reaches 97.06%. The problem-based learning (PBL) learning model can improve learning outcomes in the Chemical Industry Process course.